New mammography screening performance metrics based on the entire screening episode - Sprague, Brian L. (Cancer, 2020)
BACKGROUND: Established mammography screening performance metrics use the initial screening mammography assessment because they were developed for radiologist performance auditing, yet these metrics are frequently used to inform health policy and screening decision-making. We developed new performance metrics based on the final assessment that consider the entire screening episode, including diagnostic work-up. METHODS: We used data from 2,512,577 screening episodes during 2005–2017 at 146 facilities in the United States participating in the Breast Cancer Surveillance Consortium. We compared screening performance metrics based on the final assessment of the screening episode to conventional metrics defined using the initial assessment. We also stratified results by breast density and breast cancer risk. RESULTS: The cancer detection rate was similar for final (4.1 per 1000; 95% CI: 3.8–4.3) vs. initial assessment (4.1 per 1000; 95% CI: 3.9–4.3). The interval cancer rate was 12% higher based on final (0.77 per 1000; 95% CI: 0.71–0.83) vs. initial assessment (0.69 per 1000; 95% CI: 0.64–0.74), resulting in a modest difference in sensitivity (84.1% [95% CI: 83.0–85.1] vs. 85.7% [95% CI: 84.8–86.6%], respectively). Absolute differences in interval cancer rate between final and initial assessment increased with breast density and breast cancer risk (e.g., difference of 0.29 per 1000 for women with extremely dense breasts and 5-year risk >2.49%). CONCLUSIONS: Established screening performance metrics underestimate the interval cancer rate of a mammography screening episode, particularly for women with dense breasts or elevated breast cancer risk. Women, clinicians, policymakers, and researchers should use final assessment performance metrics to support informed screening decisions.